Ureido Derivatives of Neoabietic Acid - Gao, Xinyu; Feng, Niping; Zi, Yuhan; Cao, Jianguo; Huang, Guozheng (MolBank, 2018)
A series of ureido derivatives of neoabietic acid were synthesized by application of Curtius rearrangement reaction to neoabietic acid and amines. Structure characterization of these compounds was done by 1H-NMR, 13C-NMR and HRMS spectral analysis.